Pythagorean Fuzzy HX Bi – Ideals in HX- Near Rings - M. Himaya Jaleela Begum, G. Rama (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This article introduces the notion of Pythagorean Fuzzy HX Bi-Ideals in HX Near Rings and delves into their relevant properties. Moreover, we examine the homomorphic image and pre-image of these bi-ideals and analyze various related theorems. Throughout our analysis, we find that Pythagorean fuzzy HX bi-ideals play a crucial role in the study of HX Near Rings, and offer valuable insights into their structure and properties. By exploring the various properties and theorems associated with these Bi-Ideals, we gain a deeper understanding of their significance and potential applications in a wide range of fields. Overall, our research contributes to the ongoing exploration and development of HX Near Rings, and opens up exciting new avenues for future research in this area. We hope that our findings will inspire further study and investigation, and contribute to the advancement of this important field of mathematics.